Plant-based, fast-food, Western-contemporary, and animal-based dietary patterns and risk of premature aging in adult survivors of childhood cancer: a cross-sectional study - Tuo Lan; Mei Wang; AnnaLynn M. Williams; Matthew J. Ehrhardt; Jennifer Q. Lanctot; Shu Jiang; Kevin R. Krull; Gregory T. Armstrong; Melissa M. Hudson; Graham A. Colditz; Leslie L. Robison; Kirsten K. Ness; et al. (BMC Medicine)
Abstract Background Although premature aging is a significant concern in adult survivors of childhood cancer, little is known about the role of diet in premature aging in this vulnerable population. Therefore, we examined whether dietary patterns specific to childhood cancer survivors are associated with premature aging. Methods This cross-sectional study included 2904 adult survivors of childhood cancer (mean age = 31 years, SD = 8 years) in the St. Jude Lifetime Cohort. Diet was assessed using a food frequency. Four dietary patterns were identified: (1) plant-based diet pattern high in whole grains, fruit, and vegetables; (2) fast-food diet pattern high in processed meat, high-fat dairy, and sweets and desserts; (3) Western contemporary diet pattern high in red meat, pasta/rice, French fries, and salty snacks; and (4) animal-based diet pattern high in all meats. The deficit accumulation index (DAI), a proxy measure of premature aging, was estimated as the ratio of the number of age-related items out of 44 total conditions and categorized into low, medium, and high deficit accumulation groups. Multivariable multinomial logistic regressions were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of medium and high DAI groups (reference: low group). Results Compared to survivors consuming a plant-based diet, those who consume a fast-food (ORhigh vs. low DAI = 1.82, 95% CI: 1.12‒2.96), a Western contemporary (OR = 2.12, 95% CI: 1.31‒3.43), or an animal-based diet (OR = 2.10, 95% CI: 1.15‒3.84) had approximately a twofold higher odds of being in the high DAI group. In contrast, survivors with a plant-based diet had almost 50% lower odds of being in the high DAI group, compared to those with other dietary patterns (OR ranges 0.47‒0.55). Conclusions A plant-based diet may promote healthy aging, whereas a fast-food, a Western contemporary, and an animal-based diet may have detrimental effects on aging. Adult survivors of childhood cancer may benefit from nutrition education and interventions for healthy aging.